Considerations for single and double leg drop jumps: Bilateral deficit, standardizing drop height, and equalizing training load - Pain, M. T. G. (Journal of Applied Biomechanics, 2014)
Bilateral deficit is well documented; however, bilateral deficit is not present in all tasks and is more likely in dynamic activities than isometric activities. No definitive mechanism(s) for bilateral deficit is known but an oft cited mechanism is lower activation of fast twitch motor units. The aim of this study was to produce comparable and consistent one and two legged drop jumps to examine bilateral deficit in elite power athletes and elite endurance athletes. Seven power athletes and seven endurance athletes performed single and double leg drop jumps from a range of heights that equalized loading per leg in terms of: height dropped, energy absorbed, and momentum absorbed. Force and motion data were collected at 800 Hz. Bilateral deficit for jump height, peak concentric force, and peak concentric power were calculated. Power athletes had a significantly greater (P < .05) bilateral deficit for jump height and peak power, possibly due to power athletes having more fast twitch motor units, however, endurance athletes generally had a bilateral surfeit which could confound this inference. Results indicate that equalizing loading by impulse per leg is the most appropriate and that a consistent drop height can be obtained with a short 10 minute coaching session.